Routledge Handbook of U.S. Counterterrorism and Irregular Warfare Operations - Sheehan, Michael A.; Marquardt, Erich; Collins, Liam (Taylor & Francis, 2022)
This handbook comprises essays by leading scholars and practitioners on the topic of U.S. counterterrorism and irregular warfare campaigns and operations around the globe. Terrorist groups have evolved substantially since 9/11, with the Islamic State often described as a pseudo-state, a terrorist group, and insurgency all at the same time. While researchers', analysts', and policymakers' understanding of terrorism has grown immensely over the past two decades, similar advancements in the understanding of counterterrorism lag. As such, this handbook explains why it is necessary to take a broader view of counterterrorism which can, and often does, include irregular warfare. The volume is divided into three thematic sections: Part I examines modern terrorism in the Islamic world and gives an overview of the major terrorist groups from the past three decades; Part II provides a wide variety of case studies of counterterrorism and irregular warfare operations, spanning from the 1980s to the irregular warfare campaign against the Islamic State in northern Syria in 2018; Part III examines the government instruments used to combat terrorism and wage irregular warfare, such as drones, Theater Special Operations Commands, and Theater Commands. The handbook fills a gap in the traditional counterterrorism literature by its inclusion of irregular warfare and by providing analyses from academic experts as well as practitioners. It will be of much interest to students of counterterrorism, counterinsurgency, U.S. national security, military affairs, and International Relations. The Open Access version of this book, available at https://www.routledge.com/Routledge-Handbook-of-US-Counterterrorism-and-Irregular-Warfare-Operations/Sheehan-Marquardt-Collins/p/book/9780367758363, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.